2013
DOI: 10.1097/aln.0b013e3182833fae
|View full text |Cite
|
Sign up to set email alerts
|

Dual Effects of Isoflurane on Proliferation, Differentiation, and Survival in Human Neuroprogenitor Cells

Abstract: Background Previous studies have demonstrated that isoflurane can provide both neuroprotection and neurotoxicity in various tissue culture models and in rodent developing brains. The cellular and molecular mechanisms mediating these dual effects are not clear, but the exposure level and duration of isoflurane appear to be determinant factors. Methods Using the ReNcell CX human neural progenitor cell line, we investigated the impact of prolonged exposure to varying isoflurane concentrations on cell survival a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 58 publications
3
71
0
2
Order By: Relevance
“…Some anesthetics, e.g., isoflurane, have been shown to induce neurotoxicity and neurobehavioral deficits in vitro and in vivo [25,[33][34][35][36][37][38][39][40][41][42][43][44][45][46]. Therefore, the current findings that propofol attenuated Aβ levels in brain tissues of mice suggested that more studies are needed to assess whether propofol could be a better choice when providing anesthesia care for AD patients or senior patients who are vulnerable to develop postoperative cognitive dysfunction.…”
Section: Discussionmentioning
confidence: 85%
“…Some anesthetics, e.g., isoflurane, have been shown to induce neurotoxicity and neurobehavioral deficits in vitro and in vivo [25,[33][34][35][36][37][38][39][40][41][42][43][44][45][46]. Therefore, the current findings that propofol attenuated Aβ levels in brain tissues of mice suggested that more studies are needed to assess whether propofol could be a better choice when providing anesthesia care for AD patients or senior patients who are vulnerable to develop postoperative cognitive dysfunction.…”
Section: Discussionmentioning
confidence: 85%
“…Isoflurane has been demonstrated to act via activation of inositol-1,4,5-trisphosphate (IP3) receptors and also cause change in intracellular calcium homeostasis Yang et al, 2008;Zhao et al, 2013). Isoflurane causes intense calcium release from the endoplasmic reticulum than sevoflurane or desflurane Yang et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Development of an in vitro neurogenesis system using human stem cells has opened up avenues of research for advancing our understanding of human brain development and the issues relevant to anesthetic-induced developmental toxicity in human neuronal lineages under controlled conditions. Recent studies from our and other groups, showed that isoflurane influenced human NSC proliferation and neurogenesis [47] and ketamine dose- and time-dependently induced hESC-derived neuron death [43]. Additionally, when cells underwent different lengths of exposure to propofol and were subjected to single and multiple exposures, propofol induced cell death in the hESC-derived neurons in a time, dose, and exposure number-dependent manner [45].…”
Section: Evidence Of Developmental Neurotoxicity From Different Modelsmentioning
confidence: 99%